2009
DOI: 10.1016/j.neuroscience.2009.07.045
|View full text |Cite
|
Sign up to set email alerts
|

The novel distribution of phosphodiesterase-4 subtypes within the rat retina

Abstract: Phosphodiesterases (PDEs) are important regulators of signal transduction processes. While much is known about the function of cyclic GMP specific PDEs in the retina, much less is known about the closely related, cyclic AMP specific PDEs. The purpose of the present study is to characterize and localize PDE4 within the adult rat retina. We have used western blotting, RT-PCR, and immunohistochemistry together with retrograde labeling to determine the presence and location of each PDE4 subtype. Western blot analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 121 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…Differential distribution of PDE proteins lead to compartmentalization of cAMP signaling (Houslay et al, 2007, Huston et al, 2008). We have previously reported that PDE4 proteins are differentially expressed within the retina (Whitaker and Cooper, 2007). Variable PDE distributions may provide a potential mechanism to segregate Epac signaling from PKA (Huston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential distribution of PDE proteins lead to compartmentalization of cAMP signaling (Houslay et al, 2007, Huston et al, 2008). We have previously reported that PDE4 proteins are differentially expressed within the retina (Whitaker and Cooper, 2007). Variable PDE distributions may provide a potential mechanism to segregate Epac signaling from PKA (Huston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical studies of adenylate cyclase, the protein responsible for cAMP production, have revealed that 9 splice variants are present and differentially expressed throughout the retina (Abdel-Majid et al, 2002). Similarly, phosphodiesterases (PDEs), proteins responsible for hydrolyzing cyclic nucleotides, are expressed within the retina (Santone et al, 2006, Whitaker and Cooper, 2007). Thus, to better understand the function of cAMP within the retina, a focus on the distribution of functionally related proteins such as the exchange proteins directly-activated by cAMP is in order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PDE with IBMX enhanced the responses elicited by the diterpene activator of adenylyl cyclase, forskolin suggesting that catabolism of cyclic AMP does occur in these tissues. Indeed, there is evidence that PDE is present in several retinal cells such as the ganglion, bipolar, horizontal, amacrine and rod photoreceptors [32]. We included IBMX in all subsequent studies on the effects of H 2 S donors on cyclic AMP production in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In double immunostaining, these DGKι-positive puncta were shown to be apposed side-by-side and never overlapped with immunoreactivity for vesicular glutamate transporter 1 (VGluT1), a marker for ribbon synapses of photoreceptor terminals in the OPL (Whitaker and Cooper 2009) (Fig. 2A,B).…”
Section: Dgkιmentioning
confidence: 99%